A new species of Reichardia (Asteraceae, Cichorieae) from Albania and re-evaluation of R. macrophylla - Conti, Fabio; Niketić, Marjan; Vukojičić, Snežana; Siljak-Yakovlev, Sonja; Barina, Zoltán; Lakušić, Dmitar (Phytotaxa, 2015)
Reichardia albanica, a new species from Mount Çika (Albanian: Mali i Çikës) in southern Albania, is described and illustrated. Its relationship with the closest taxa is also discussed and a key for the identification of species in Balkan Peninsula and Turkey is provided. In addition R. macrophylla, a neglected and synonymized Balkan endemic species, has been re-evaluated. The name Picridium macrophyllum has been lectotypified.